The Influence of ESG Disclosure, Corporate Governance, and Financial Performance on Dividend Policy in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) During 2018–2022 - Tondang, Riris Desy R; Wedari, Linda Kusumaning (Dinasti Publisher, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) disclosure, corporate governance (board size), and financial performance (ROA and ROE) on dividend policy among manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Using a quantitative approach with panel data regression and purposive sampling, 45 companies from the Basic Materials and Consumer Non-Cyclicals sectors were analyzed, resulting in 225 observations. The Fixed Effects Model (FEM) was employed based on the results of Chow and Hausman tests. The findings reveal that ESG disclosure, board size, ROA, and ROE each have a statistically significant positive effect on the Dividend Payout Ratio (DPR). This implies that companies with higher ESG performance, better governance structures, and strong profitability are more likely to distribute dividends. The study supports stakeholder theory, agency theory, and signaling theory, highlighting that non-financial disclosures such as ESG play a vital role in enhancing stakeholder trust and shaping dividend decisions. These results contribute to the growing literature on sustainable finance and offer practical insights for investors, regulators, and corporate decision-makers. The research underscores the importance of integrating ESG and good corporate governance into strategic financial policies, especially in the context of post-pandemic recovery and green economic transition.